Piperine loaded zinc oxide nanocomposite inhibits the PI3K/AKT/mTOR signaling pathway via attenuating the development of gastric carcinoma: In vitro and in vivo studies - Zhen Yang; Minglong Pu; Xinhua Dong; Feihong Ji; Vishnu Priya Veeraraghavan; Hongwei Yang (Arabian Journal of Chemistry, 2020)
Gastric cancer (GC) is the fifth most cancer type and the third most cause of cancer-associated deaths worldwide along with the 5-year survival rate is less the 30%. This investigation was aimed to synthesis the piperine-loaded zinc oxide nanocomposite (ZnO-Pip-NC) and investigating its anticancer activity against the GC by in vitro and in vivo models by the inhibiting the apoptotic and PI3K/Akt/mTOR signaling pathways. The synthesized ZnO-Pip-NC was characterized by different techniques. The cytotoxicity of zinc oxide, piperine and the formulated ZnO-Pip-NC was tested against the AGS cells by MTT assay. The intracellular ROS level, mitochondrial membrane potential, and apoptotic cell necrosis in the AGS cells was examined by fluorescent staining techniques. The expression of apoptotic and PI3K/Akt/mTOR signaling markers were inspected by western blotting and the expression of pro0inflammatory markers analyzed by RT-PCR technique. The antioxidant levels were examined by standard methods and histopathology of gastric mucosa was analyzed. The ZnO-Pip-NC treatment appreciably inhibited the AGS cell viability. ZnO-Pip-NC treated cells also exhibited excessive intracellular ROS, diminished MMP, nuclear damages, and apoptosis induction in AGS cells. The enhanced expression of pro-apoptotic proteins and inhibition of PI3K/Akt/mTOR signaling pathway was noted in ZnO-Pip-NC treated cells. In vivo studies proved that the ZnO-Pip-NC noticeably restored the antioxidants in the GC animals and also prevented the gastric mucosa and inhibited the GC tumor formation. In conclusion, the findings of this investigation confirmed the anticancer potential of ZnO-Pip-NC against the GC via inhibiting the PI3K/Akt/mTOR signaling pathway.